The impact of water and technology on the stock market in China and Japan based on a new heuristic model - Lu, Haoyang; Tang, Yajiao; Yu, Zhexi; Tan, Dan (Frontiers in Environmental Science, 2023)
Introduction: Water, as an essential strategic resource, is diminishing; this has been framed as a financial risk. We aim to quantitively investigate the impact of water use and technology on stock market and compare the differences in China and Japan, which represent emerging and mature markets, respectively. Method: We constructed three models using the difference GMM. The first and second models focused on how water use could influence the stock market volatility and return; the third model added technology as an interaction to explore its impact on the above mechanism. We used ARIMA-EGARCH model to predict the trend of marginal stock market return with an increase in industrial water use in the next 5 years. Results and Discussion: The results show that (1) water use increases the stock market volatility in both countries, but Japan shows a greater increase compared to China; (2) water use has a negative impact on the stock market return in China and a positive impact on that in Japan; (3) technology has played a positive impact role in the second model, while the ARIMA-EGARCH results correspond to the first two conclusions, which verifies the reasonability of the models. We conclude that heterogeneity exists in the two different market types because of the levels of technology.